ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK TOKO SEPATU BATA DENGAN MINAT BELI SEBAGAI MEDIASI (STUDI PADA KONSUMEN TOKO SEPATU BATA SEMARANG) - Hasyyati, Rr Diva Putri Hasyyati; Khasanah, Imroatul (Diponegoro Journal of Management, 2019)
The purpose of this study to analyze the effect of product quality, perceived price and brand image on purchase intention and the impact on purchase decision. The population used in this study are consumers of Toko Sepatu Bata Semarang. The number of samples used in this study were 110 respondents. The method of data collection is done through a questionnaire. This study uses Structural Equation Modeling (SEM) analysis techniques with AMOS 23.0 analysis tool.The results of this study show that product quality has a positive and significant effect on purchase intention, product quality does not have significant on purchase decision, perceived price has a positive and significant effect on purchase intention, perceived price does not have significant on purchase decision, brand image has a positive and significant effect on purchase intention, brand image does not have significant on purchase decision, and purchase intention has a positive and significant effect on purchase decision.